( 蘇軾〈與謝民師推官書〉論析 ) = A study of Su Shi’s letter to Xie Minshi - 衣若芬 I, Lo-fen (2014)
蘇軾〈與謝民師推官書〉作於1100年，即其去世前一年，是回覆謝民師有關散文寫作的一封書信，信中提出「文理自然」、「辭達」的寫作理念，可謂其終生散文寫作的思想精華。〈與謝民師推官書〉的墨跡現藏上海博物館，卷後有陳繼儒、董其昌等人的題跋，分析蘇軾的書法特色。本文擬從文字內容和書法形式等方面，探討蘇軾對於散文、辭賦的文體觀念，以及「行雲流水」在文學創作和書法表現上的具體實例。Su Shi's letter to Xie Minshi "YuXie Minshi Tui Guan Shu" was written in 1100, one year before his death. The contents gave an account of prose writing; he brought up literary concepts of "Wenli Ziran" and "Cida" in this letter. He feels that literary works should be a reflection of the objective world, natural and diverse. "Cida" refers not just to grasp of the main theme of the writing and clarity in expression but also to the style of language used. This letter may be considered as the essence of his lifetime work pertaining to prose writing. The letter is now in the possession of Shanghai Museum. On the back of the scroll is written, Chen Jim and Dong Qichang's comments and analysis amongst others, of his calligraphy. This paper explores Su Shi's views towards prose writing, the "Cifu" ancient style of writing as well as his bold and restrained style of writing prolific in his literary creation and calligraphy. It is attempted from various angles such as the letter contents and calligraphy styles.